Cerebral changes in Poliomyelitis survivors: A computational neuroimaging study - Li Hi Shing, Stacey (Trinity College Dublin. School of Medicine. Discipline of Clinical Medicine, 2023)
Post-polio syndrome (PPS) is a slowly progressive LMN condition that affects 20-85% of polio survivors many decades after their initial acute infection. While motor dysfunction is the hallmark of the disease, extra-motor features such as generalised fatigue, decreased endurance, sleep disturbance, chronic pain, neuropsychological deficits, sensory impairments and cold intolerance have also been reported. PPS is a multi-system condition with considerable quality of life implications with no established aetiology, confirmed pathophysiology and patterns of cerebral involvement. There is a striking paucity of PPS post-mortem and imaging studies compared to other MND phenotypes and the evidence of cerebral involvement remains conflicting. PPS is a diagnosis of exclusion and the mainstay treatment remains supportive and no disease modifying therapy currently exists. The main aim of this research study was the in-depth characterisation of PPS-associated cerebral changes using high resolution structural and diffusion MRI. Extra-motor cortical, subcortical and cerebellar involvement were specifically assessed. The associated brain changes were contrasted to cerebral involvement in amyotrophic lateral sclerosis (ALS), a mixed UMN/LMN motor neuron disease. In this prospective, single-centre neuroimaging study, a total of 43 adult polio survivors were recruited, assessed using standardised clinical assessments and underwent high-resolution 3T MRI. The imaging profile of the adult polio survivors were compared to 117 healthy controls (HC) and 88 patients with amyotrophic lateral sclerosis (ALS). Whole-brain and region-of-interest morphometric analyses were undertaken to evaluate patterns of grey matter changes. Tract-based spatial statistics were performed to assess diffusivity alterations within the white matter skeleton. Furthermore, cortical thickness measurements, subcortical volumetry, brainstem, thalamic and amygdalar segmentation were performed. Cerebellar changes were evaluated using cortical thickness and volume analyses, morphometry and voxel-wise white matter analyses to appraise the cerebellar peduncles. Adult polio survivors exhibited high levels of motor dysfunction affecting predominantly their lower limbs. Extra-motor features were detected in this cohort using our screening tools and included high prevalence of problematic fatigue, verbal fluency and language deficits and apathy. Poliomyelitis survivors exhibited increased grey matter partial volumes within the brainstem, occipital love and cerebellum accompanied by increased WM integrity in the corticospinal tract, cerebellum, bilateral mesial temporal lobes and inferior frontal tracts. Furthermore, polio survivors demonstrated increased cortical thickness within cerebellar lobules I,II and III of the right anterior lobe and lobules VIIIA and VIIIB bilaterally accompanied by enhanced cerebellar peduncular organisation particularly within the middle cerebellar peduncles. Limited atrophy were denoted within the cingulate gyrus, temporal pole and left nucleus accumbens when contrasted to healthy controls. Overall, these findings suggest a structural cortical and cerebellar reorganisation in poliomyelitis survivors which may represent adaptive changes to severe lower motor neuron injury in early life and as a result of ensuing motor disability.
APPROVED
Keywords: Poliomyelitis; Motor neuron disease; Neuroimaging; MRI; Neuroplasticity; Post-polio syndrome